The relationship of loneliness and attitude towards social deviances among nursing and health students during the coronavirus 2019 pandemic - Fatemeh Pashapour; Abbas Shamsalinia; Mahboobeh Daneshnia; Niloofar Alavii; Fatemeh Zahrah Pourabdollah; Fatemeh Mohammadkhah (Shahrekord University of Medical Sciences, 2021)
Background and aims: Loneliness can increase stress, anxiety, and engagement in social deviances (SDs) among adolescents and youngsters. The present study was conducted to evaluate the relationship of loneliness and attitude towards SDs among nursing and health students during the coronavirus disease 2019 pandemic. Methods: This cross-sectional descriptive-analytical study was conducted in 2020. Participants were 105 nursing and health students of Ramsar Faculty of Nursing, Mazandaran, Iran. Data were collected using the Revised UCLA Loneliness Scale and the Social Deviances Attitude Scale. Data were entered into the SPSS software (v. 16.0) and analyzed through the independent-sample t, Mann Whitney U, and Kruskal-Wallis tests, the analysis of variance, the Spearman's correlation analysis, and the multiple regression analysis. Results: Most participants were female (73.3%) and single (90.5%) and studied nursing (55.2%). The mean scores of loneliness and attitude towards SDs were 40.19±10.51 and 68.57±8.32, respectively. The highest dimensional score of attitude towards SDs was related to the drug abuse dimension (15.31±2.65). Loneliness had significant relationship with attitude towards SDs and all its dimensions (P<0.05). The significant predictors of loneliness were attitude towards SDs, its aggression dimension, family income, father's occupation, and father's educational level (P<0.05). Conclusion: Students have low level of loneliness and negative attitude towards SDs. Attitude towards SDs, its aggression dimension, family income, father's occupation, and father's educational level are the significant predictors of loneliness. Health and education policy makers need to use strategies to reduce students' loneliness in order to reduce the risk of their engagement in SDs.